2018
DOI: 10.3389/fmicb.2018.02036
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of Lysine Acetylation in Borrelia burgdorferi B31 Reveals Its Role in Central Metabolism

Abstract: The post-translational modification of proteins has been shown to be extremely important in prokaryotes. Using a highly sensitive mass spectrometry-based proteomics approach, we have characterized the acetylome of B. burgdorferi. As previously reported for other bacteria, a relatively low number (5%) of the potential genome-encoded proteins of B. burgdorferi were acetylated. Of these, the vast majority were involved in central metabolism and cellular information processing (transcription, translation, etc.). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 82 publications
(125 reference statements)
2
22
0
Order By: Relevance
“…The mechanisms governing the development of persister cells are not easily discerned by these RNASeq analyses, perhaps because the spirochetes stochastically enter dormancy (Caskey and Embers, 2015) and regrowth is determined by non-heritable traits. One supposition may be that instead, post-transcriptional, or even post-translational events such as lysine acetylation (Fisher et al, 2017; Bontemps-Gallo et al, 2018) govern the entry and exit from dormancy in the antibiotic environment. For example, in the toxin-mediated growth reduction within S. typhimurium , the toxins (TacT) add a post-translational modification (acetylation) to tRNA, which is reversed by a peptidyl tRNA hydrolase (Cheverton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms governing the development of persister cells are not easily discerned by these RNASeq analyses, perhaps because the spirochetes stochastically enter dormancy (Caskey and Embers, 2015) and regrowth is determined by non-heritable traits. One supposition may be that instead, post-transcriptional, or even post-translational events such as lysine acetylation (Fisher et al, 2017; Bontemps-Gallo et al, 2018) govern the entry and exit from dormancy in the antibiotic environment. For example, in the toxin-mediated growth reduction within S. typhimurium , the toxins (TacT) add a post-translational modification (acetylation) to tRNA, which is reversed by a peptidyl tRNA hydrolase (Cheverton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the extent of acetylation, the mechanisms by which acetylation occurs, the identities of acetylated proteins, and the locations of acetylation on those proteins can vary between organisms; yet, in most cases, there is great conservation in core cellular processes (Nakayasu et al, 2017). Such approaches have shown that acetylation occurs on proteins involved in a wide diversity of cellular process, especially central metabolism and translation (Wang et al, 2010; Weinert et al, 2013a; Baeza et al, 2014; Kuhn et al, 2014; Kosono et al, 2015; Schilling et al, 2015; Kentache et al, 2016; Birhanu et al, 2017; Jers et al, 2017; Nagano-Shoji et al, 2017; Post et al, 2017; Bontemps-Gallo et al, 2018; Gaviard et al, 2018; Sun et al, 2018; Vasileva et al, 2018; Yoshida et al, 2019). As stated above, many of these acetylations are conserved.…”
Section: Mass Spectrometry-based Proteomics To Study Bacterial Acetylmentioning
confidence: 99%
“…Furthermore, attempts to reduce the levels of AcCoA, such as by draining acetyl groups into an acetyl group polymer such as polyhydroxybutyrate, do not avoid any contribution by KATs (Hu, 2013). Work in an organism where AcCoA can be non-essential, such as the reduced genome bacterium Borrelia burgdorferi that solely synthesizes AcCoA to generate mevalonate, a precursor of cell wall lipid I, might be a useful reductionist system to determine whether this truly occurs in vivo (Bontemps-Gallo et al, 2018). Without knowing all possible KATs and eliminating them, it is hard to truly ever say whether an AcCoA-dependent acetylation is truly non-enzymatic in vivo .…”
Section: Non-enzymatic Acetylation Via Acp and Accoamentioning
confidence: 99%
“…In a few cases, we know that acetylation of a lysine can affect protein function (1, 2, 20, 137, 186193). However, there remain thousands of acetyllysines without functional assessment.…”
Section: Introductionmentioning
confidence: 99%